Revisiting Concept and Development of Sustainability Reporting in Banking Research: A Bibliometric Approach - Muhammad (SMART Insight, 2021)
The concept of sustainability has become one of the new business concerns for all industries, including the banking industry. Furthermore, the industry is under various internal and external pressures to adopt this concept in its business implementation. This concept emphasizes the balance of three aspects: environmental, social, and economic. In order to communicate sustainability aspects to stakeholders, the industry carries out sustainability reporting as one of the initiatives. Along with the implementation of sustainability reporting, related research began to develop by utilizing available reports. Therefore, this study aims to provide quantitative information on the development of sustainability reporting in the banking literature. There are 94 papers in journals, book chapters, conference papers indexed by the Scopus database from 2000-2021. We employed VOSViewer and Excel software to synthesize and analyze the data. This research is limited to the Scopus database and banking sector. In addition, we provide an extensive section to review some relevant papers that directly talk about sustainability reporting in the banking sector.